Gambaran Status Gizi Balita Pada Masa Pandemi Covid-19 Di Wilayah Kerja Puskesmas Kaliwates - Ririn Handayani (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2022)
Indonesia is one of the countries with the highest child mortality rate due to Covid-19 which is 2.5 percent. One of the causes of the high child mortality rate is the low level of child health examinations, the status of children with congenital disorders and children with poor nutritional status. Increasing immunity needs to be done to prevent morbidity in children. One of them is by eating balanced nutrition, maintaining health protocols, wearing masks and avoiding crowds. The purpose of this study was to identify the nutritional status of toddlers during the Covid-19 pandemic. Research of methods is descriptive, cross sectional approach. Subjects in this study were all toddlers in Posyandu Aster 11 and 15 as much 91 children. Methods of collecting data by measuring TB and BB. Measurement results analyzed using a table of categories of nutritional status of toddlers to WHO. Data analysis used the frequency distribution. Analysis result were based on TB/U (45% in the very short category, 9% short, 46%). ), analysis based on BB/TB (2% with very thin category, 3% thin, 65% normal, 30% fat). Research conclution that most of toddlers have good nutritional status, although there are toddlers of poor nutritional status and there are toddlers with category of very short (stunting).